The Relationship between SES and Reading Comprehension in Chinese: A Mediation Model - Cheng, Yahua; Wu, Xinchun (Frontiers in Psychology, 2017)
An increasing body of research provides evidence that socioeconomic status (SES) was significantly related to children’s reading development; however, the psychological mechanism underlying the association between them remained an open question. The present study is designed to test the hypothesized three-path effect of vocabulary knowledge and morphological awareness as mediators between SES and sentence reading comprehension in Chinese first-graders. Results of mediation model showed that SES exerted its effect on sentence reading comprehension through the indirect path via the simple mediating effect of morphological awareness and the three-path mediating effect of vocabulary knowledge and morphological awareness. The findings highlight a previously unidentified mechanism of the relationship between SES and reading comprehension in Chinese young children.